Female labor force participation and development - Sher Verick (IZA World of Labor, 2018)
The relationship between female labor force participation and economic development is far more complex than often portrayed in both the academic literature and policy debates. Due to various economic and social factors, such as the pattern of growth, education attainment, and social norms, trends in female labor force participation do not conform consistently with the notion of a U-shaped relationship with GDP. Beyond participation rates, policymakers need to focus on improving women's access to quality employment.
Keywords: J16; J21; J22; O11; O12; 330; female labor force participation; developing countries; employment